Neuroinflammation in Alzheimer's disease and beneficial action of luteolin. (21st February 2021) - Delgado, Alejandro; Cholevas, Christos; Theoharides, Theoharis C.
Abstract: Alzheimer's disease (AD), already the world's most common form of dementia, is projected to continue increasing in prevalence over the next several decades. The current lack of understanding of the pathogenesis of AD has hampered the development of effective treatments. Historically, AD research has been predicated on the amyloid cascade hypothesis (ACH), which attributes disease progression to the build‐up of amyloid protein. However, multiple clinical studies of drugs interfering with ACH have failed to show any benefit demonstrating that AD etiology is more complex than previously thought. Here we review the current literature on the emerging key role of neuroinflammation, especially activation of microglia, in AD pathogenesis. Moreover, we provide compelling evidence that certain flavonoids, especially luteolin formulated in olive pomace oil together with hydroxytyrosol, offers a reasonable prophylactic treatment approach due to its many beneficial actions.